Assessing spatial and temporal changes in diversity of copepod crustaceans: a key step for biodiversity conservation in groundwater-fed springs - Cerasoli, Francesco; Fiasca, Barbara; Di Lorenzo, Tiziana; Lombardi, Annalina; Tomassetti, Barbara; Lorenzi, Valeria; Vaccarelli, Ilaria; Di Cicco, Mattia; Petitta, Marco; Galassi, Diana M. P. (Frontiers in Environmental Science, 2023)
Despite the close attention springs have received from a hydrologic perspective and as biodiversity hotspots, the multiple dimensions of diversity of spring meiofaunal assemblages are still poorly investigated. Knowledge of beta diversity patterns and drivers can inform and improve management decisions on biodiversity conservation. Here, we analyzed beta diversity of copepod assemblages in karst springs in Central Italy by focusing on: 1) relative contributions of turnover and nestedness components to taxonomic and phylogenetic beta diversity; 2) temporal variation of species richness and beta diversity within and between the target springs in conjunction with models of the influence of physical-chemical parameters on within-spring diversity changes; 3) expected risk of habitat loss due to variation in groundwater recharge under climate change. To this end, we gathered data from 168 samples collected in four karst springs from 2004 to 2016. Overall, we found 48 copepod species, 22 of which are obligate groundwater dwellers while the remaining 26 usually occur in surface freshwaters. All springs showed significant changes in taxonomic and phylogenetic beta diversity over time. Total beta diversity was high for both the taxonomic and phylogenetic dimensions, and turnover was the main component. Inter-site variability in dissolved oxygen explained a noticeable part of temporal variation in beta diversity, likely reflecting the role of microhabitat heterogeneity in shaping site-specific assemblages. However, most of temporal variation in species richness and beta diversity remained unexplained, suggesting a major role of other factors, such as seasonal discharge variations. Modelling of recharge rates for all the four springs over 2001-2020 suggested a potential > 40% recharge deficit under dry conditions. Moreover, Cellular Automata-based modelling of rainfall over the Gran Sasso-Sirente hydrogeological unit (feeding three of the four springs) predicted an overall precipitation decrease in the 2081-2095 period. Such changes could produce severe effects on springs’ microhabitats and related communities. Our results indicate that partitioning beta diversity, monitoring its temporal changes and assessing its environmental drivers are critical to evidence-based conservation of springs. Particularly, the high species turnover we have observed suggests that conservation strategies should seek to preserve as many microhabitats as possible within and among karst springs.